An integrated intelligent paradigm to detect DDoS attack in mobile ad hoc networks. (2016) - Devi, P.; Kannammal, A.
Various types of routing attacks and their corresponding countermeasures for mobile ad hoc networks (MANETs) have been identified in the literature study. However problems of computational complexity and false alarms have not yet been reduced. In this paper, we have proposed a proactive detection mechanism for distributed denial of service (DDoS) which considers feature extraction, reduction of entropy, clustering technique and feature ranking. These techniques are approached by statistical analysis and involved for XOR marking to classify legitimate and malicious data packets. Our system applies detection methodologies on each packet, finds abnormalities during the pre-attack phase itself and filters them. Experiments are done with the 2000 DARPA intrusion detection scenario specific dataset to assess detection time, ratio of false alarms, and complexity. The experimental results show the efficiency of proposed system in detection of DDoS attack with larger reduction of false positive and computational complexity.